Political institutions in Europe - Colomer, Josep Maria (Routledge, 2002)
Great Britain and Ireland : variations of party government / Ian Budge -- Germany : the grand coalition state / Manfred G. Schmidt -- France : the institutionalization of leadership / Yves Mény -- Italy : a democratic regime in transition / Gianfranco Pasquino -- Spain and Portugal : rule by party leadership / Josep M. Colomer -- The Low Countries : confrontation and co-operation in segmented societies / Hans Keman -- The Nordic countries : contention, compromise and corporatism / Jan-Erik Lane and Svante Ersson -- The European Union : federalism in the making / Josep M. Colomer
Literaturangaben
Keywords: Europe -- Politics and government; Aufsatzsammlung; Politische Institution; Europäische Union; Internationaler Vergleich; Westeuropa; Politisches System